2020
DOI: 10.1111/aspp.12561
|View full text |Cite
|
Sign up to set email alerts
|

Indian media coverage of Nizamuddin Markaz event during COVID‐19 pandemic

Abstract: The corona virus pandemic, apart from being an economic and human tragedy, has affected the socio-fabric of India by increasing hate, xenophobia, and prejudices against minorities. Thus, an analysis of Indian media, with respect to COVID-19 spread, becomes important. A religious congregation organized by Jammat e Islami, a global religious organization in Delhi, between March 1 and 21, brought more than 5,000 people from various countries to India's capital. This event led to a major spike in corona cases in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Platforms such as Facebook, Twitter, WhatsApp and the recently banned TikTok were flooded with people sharing fake images and interview clips. It was reported that Covid-19 related fake news spiked in the month of April 6 , particularly after the Tablighi Jammat in Delhi (Sharma, 2020). Fact checking websites across the country revealed that 35% of the videos circulated were fake, 29% false images 7 and other range of issues such as incorrect diagnosis and spurious treatment along with dubious guidelines.…”
Section: The Spread Of Fake Newsmentioning
confidence: 99%
“…Platforms such as Facebook, Twitter, WhatsApp and the recently banned TikTok were flooded with people sharing fake images and interview clips. It was reported that Covid-19 related fake news spiked in the month of April 6 , particularly after the Tablighi Jammat in Delhi (Sharma, 2020). Fact checking websites across the country revealed that 35% of the videos circulated were fake, 29% false images 7 and other range of issues such as incorrect diagnosis and spurious treatment along with dubious guidelines.…”
Section: The Spread Of Fake Newsmentioning
confidence: 99%
“…The government struggled to appear as a reliable source of information to them. It did not help that the media allegedly attached a religious connotation to the spread of the virus (Jena, Yadav and Rambarki, 2021;Mustafa, 2020;Sharma and Anand, 2020.…”
Section: Mistrust Of Federal Policies In Specimc Communitiesmentioning
confidence: 99%